ASOSIASI CA 125 DENGAN RESPON TERAPI PADA PENDERITA LIMFOMA NON-HODGKIN AGRESIF YANG MENDAPAT KEMOTERAPI CYCLOPHOSPHAMIDE, DOXORUBICIN, VINCRISTINE, PREDNISONE (CHOP) - S, Merlyna; Mulyono, Adi; -, Ugroseno; Putra Sedana, Made; Ashariati, Ami; -, Sugianto; -, Boediwarsono; -, Soebandiri (journal of internal medicine, 2012)
Cancer antigen (CA) 125 is a glycoprotein produced by epithelial ovarium tumors and mesothelial cells, its levels also have been shown to be elevated in patients with Non-Hodgkin!s Lymphoma (NHL). Several papers have reported an association of high CA 125 serum levels with advanced NHL as well as relationship between high CA 125 values and poor outcome. This study aimed to determine association between CA 125 levels (> 35 U/ml) with normal CA 125 (  35 U/ml) to the respone of NHL patients receiving chemotherapy CHOP. An observational analytic prospective study was done in 40 patients with NHL at Dr Soetomo Hospital Surabaya. The patient were recruited from both inpatient and outpatient clinic and the initial CA 125 level had determined before the patients received chemotherapy with Cyclophosphamide, Doxorubicin, Vincristine and Prednisone (CHOP). Of the 40 patients who included in this study, 62.5% were male, 37.5% were female, the average age 43,45 years, the most kind of histophatology result were diffuse large cell, cleaved or non cleaved cell (47.5%). There was a signiÞ cant association between CA 125 levels with therapy respone groups (responive and unresponive), with signiÞ cancy 0.001 (OR 23.22; CI 95%), and with therapy respone groups (CR, PR, NC, PD) with signiÞ cancy 0.013. The group with normal CA 125 levels (  35 U/ml), had better respone, it was around 95% responive (CR = 35%, PR = 60%) and 5% unresponive (NC = 5%, PD = 0%) than the group who had high CA 125 levels (> 35 U/ml), it was only 45% responive (CR = 15%, PR = 30% and 55% unresponive (NC = 50%, PD = 5%). As a conclusion, levels of CA 125 (> 35 U/ml) perhaps could be a negative prognostic factor to predict the CHOP chemotherapy respone in NHL patients.
Keywords: Aggressive Non-Hodgkin!s Lymphoma, CA 125